Artemídia preferente: fenômeno jogar & ler nas histórias em quadrinhos interativas (HQI) com os games de RPG - Arruda, Amanda Rigitano Ferraz de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This artistic-scientific process aims to innovate the concept of Interactive Comics by adding them into the concept of RPG games and Single-Adventures. To make it properly done, there will be some issues about Interactivity, history of the Comic Strip and Mangas, and their techniques of use. Also, there will be other issues involving Electronic Comics and Interactive Comics, in addition to the concept of the RPG games and Single-Adventures, so that the reader of this paper could understand the practical result of every issue combined into one. The identification of these issues is made from a bibliographic and iconographic research, and it will also be displayed throughout the content. Some decisions will be thrown along this paper for the reader to decide and, therefore, understand the Interactivity process in a better way. The combined issues’ result will be presented in my interactive website, http://a3studios.com.br/iss/home (address not final) or http://amstarproductions.net (final address), where the readers will have to experience the “Play&Read” phenomenon. Furthermore, this work is inserted in the line of the research Artistic Processes and Procedures of the Department of Fine Arts from the Art Institute of UNESP, whose methodology used was the Freinet Educational Cybernetics, developed in the research group Media Arts and Videoclip leaded by the leading advisor for this Final Course Work. The result and discussion of artistic and scientific research were reported in monographs such as this that I present, with the following versions: PDF version for dissemination in the virtual repository of the Institute of Arts’ Library; hardcover version for physical collection at the Library of Institute of Arts; The Printed Version for the board of examiners; and an appropriated template version for submission to International Scientific Congress in the area of Arts.

O termo “Artemídia Preferente” expressa um processo artístico-científico realizado na interface Arte-Comunicação-Ciência apresentado como Trabalho de Conclusão de Curso em Artes Visuais na modalidade Bacharelado. Na abordagem desta pesquisa artístico-científica, procura-se por inovar o conceito de História em Quadrinho Interativa (HQI), adicionando-a ao conceito dos games, dos jogos de RPG e das Aventuras-solo. Para isso, serão apresentados os assuntos sobre Interatividade, história das Histórias em Quadrinhos e dos mangás, bem como suas técnicas de uso, História em Quadrinhos Eletrônicas (HQtrônicas) e História em Quadrinhos Interativas, além do conceito de jogos de RPG e Aventuras-solo, para que o leitor possa entender o resultado prático da união de tudo isso. A identificação destes assuntos é feita a partir de um levantamento bibliográfico e iconográfico e será, também, apresentada ao longo do conteúdo. Além disso, algumas decisões serão propostas ao longo deste trabalho, para que o leitor decida o que fazer, para que a noção de interatividade seja mais bem apresentada. O resultado prático de tudo será apresentado no meu website interativo, http://a3studios.com.br/iss/home (endereço temporário) ou http://amstarproductions.net (endereço final), onde os leitores terão de vivenciar o fenômeno “Jogar&Ler”. Para complementar, o presente trabalho está inserido na linha de pesquisa “Processos e Procedimentos Artísticos” do Departamento de Artes Plásticas do Instituto de Artes da UNESP, cuja metodologia utilizada foi a Cibernética Pedagógica Freinetiana, desenvolvida no Grupo de Pesquisa “Artemídia e Videoclip”, do qual é líder o orientador deste TCC. O resultado e a discussão da pesquisa artístico-científica foram relatados em monografias, tais como esta que apresento, com as seguintes versões: Versão em PDF para divulgação em repositório ...
Keywords: Histórias em quadrinhos; Jogos; Arte interativa; Comic books, strips, etc